Yunnan Baiyao Conditioned Medium Promotes the Odonto/Osteogenic Capacity of Stem Cells from Apical Papilla via Nuclear Factor Kappa B Signaling Pathway - Pang, Xiyao (Biomed Res Int, 2019)
Yunnan Baiyao is a traditional Chinese herbal remedy that has long been used for its characteristics of wound healing, bone regeneration, and anti-inflammation. However, the effects of Yunnan Baiyao on the odonto/osteogenic differentiation of stem cells from apical papilla (SCAPs) and the potential mechanisms remain unclear. The aim of this study was to investigate the odonto/osteogenic differentiation effects of Yunnan Baiyao on SCAPs and the underlying mechanisms involved. SCAPs were isolated and cocultured with Yunnan Baiyao conditioned media. The proliferation ability was determined by cell counting kit 8 and flow cytometry. The differentiation capacity and the involvement of NF-κB pathway were investigated by alkaline phosphatase assay, alizarin red staining, immunofluorescence assay, real-time RT-PCR, and western blot analyses. Yunnan Baiyao conditioned medium at the concentration of 50 μg/mL upregulated alkaline phosphatase activity, induced more mineralized nodules, and increased the expression of odonto/osteogenic genes/proteins (e.g., OCN/OCN, OPN/OPN, OSX/OSX, RUNX2/RUNX2, ALP/ALP, COL-I/COL-I, DMP1, DSP/DSPP) of SCAPs. In addition, the expression of cytoplasmic phos-IκBα, phos-P65, and nuclear P65 was significantly increased in Yunnan Baiyao conditioned medium treated SCAPs in a time-dependent manner. Conversely, the differentiation of Yunnan Baiyao conditioned medium treated SCAPs was obviously inhibited when these stem cells were cocultured with the specific NF-κB inhibitor BMS345541. Yunnan Baiyao can promote the odonto/osteogenic differentiation of SCAPs via the NF-κB signaling pathway.